Effect of substrate temperature on microstructure and optical properties of Ga doped ZnO films deposited by pulsed laser deposition. (April 2015) - Zou, Y. S.; Wang, S. L.; Yang, H.; Wang, K.; Hui, S.
Abstract : Gallium doped ZnO (GZO) films were deposited on Si (100) and fused silica substrates by pulsed laser deposition at substrate temperature varying from 300 and 600°C. The crystal structure of the deposited film is found to be c axis preferred orientation. The X-ray diffraction results demonstrate that the crystallinity of GZO film is improved and then deteriorated when substrate temperature increases from 300 to 600°C. The average surface roughness slightly decreases from 7·2 to 5·0 nm then increases to 15·6 nm as the substrate temperature reaches 600°C. The optical band gap of the film is found to increase slightly from 3·28 to 3·33 eV with increasing substrate temperature from 300 to 600°C. The refractive index of the GZO film first increases as the substrate temperature increases from 300 to 400°C then decreases when further increases the substrate temperature to 600°C, and is in the range of 1·87–2·23.